Despite the spread of health information exchange, there is little evidence of its impact on cost, use, and quality of care - Rahurkar, Saurabh; Vest, Joshua R; Menachemi, Nir (Health affairs (Millwood, Va.), 2015)
Health information exchange (HIE), which is the transfer of electronic information such as laboratory results, clinical summaries, and medication lists, is believed to boost efficiency, reduce health care costs, and improve outcomes for patients. Stimulated by federal financial incentives, about two-thirds of hospitals and almost half of physician practices are now engaged in some type of HIE with outside organizations. To determine how HIE has affected such health care measures as cost, service use, and quality, we identified twenty-seven scientific studies, extracted selected characteristics from each, and meta-analyzed these characteristics for trends. Overall, 57 percent of published analyses reported some benefit from HIE. However, articles employing study designs having strong internal validity, such as randomized controlled trials or quasi-experiments, were significantly less likely than others to associate HIE with benefits. Among six articles with strong internal validity, one study reported paradoxical negative effects, three studies found no effect, and two studies reported that HIE led to benefits. Furthermore, these two studies had narrower focuses than the others. Overall, little generalizable evidence currently exists regarding benefits attributable to HIE.